Combining comparative proteomics and molecular genetics uncovers regulators of synaptic and axonal stability and degeneration in vivo. - Thomas M Wishart; Timothy M Rooney; Douglas J Lamont; Ann K Wright; A Jennifer Morton; Mandy Jackson; Marc R Freeman; Thomas H Gillingwater (PLoS Genetics)
Degeneration of synaptic and axonal compartments of neurons is an early event contributing to the pathogenesis of many neurodegenerative diseases, but the underlying molecular mechanisms remain unclear. Here, we demonstrate the effectiveness of a novel "top-down" approach for identifying proteins and functional pathways regulating neurodegeneration in distal compartments of neurons. A series of comparative quantitative proteomic screens on synapse-enriched fractions isolated from the mouse brain following injury identified dynamic perturbations occurring within the proteome during both initiation and onset phases of degeneration. In silico analyses highlighted significant clustering of proteins contributing to functional pathways regulating synaptic transmission and neurite development. Molecular markers of degeneration were conserved in injury and disease, with comparable responses observed in synapse-enriched fractions isolated from mouse models of Huntington's disease (HD) and spinocerebellar ataxia type 5. An initial screen targeting thirteen degeneration-associated proteins using mutant Drosophila lines revealed six potential regulators of synaptic and axonal degeneration in vivo. Mutations in CALB2, ROCK2, DNAJC5/CSP, and HIBCH partially delayed injury-induced neurodegeneration. Conversely, mutations in DNAJC6 and ALDHA1 led to spontaneous degeneration of distal axons and synapses. A more detailed genetic analysis of DNAJC5/CSP mutants confirmed that loss of DNAJC5/CSP was neuroprotective, robustly delaying degeneration in axonal and synaptic compartments. Our study has identified conserved molecular responses occurring within synapse-enriched fractions of the mouse brain during the early stages of neurodegeneration, focused on functional networks modulating synaptic transmission and incorporating molecular chaperones, cytoskeletal modifiers, and calcium-binding proteins. We propose that the proteins and functional pathways identified in the current study represent attractive targets for developing therapeutics aimed at modulating synaptic and axonal stability and neurodegeneration in vivo.